KEMAJEMUKAN GEREJA DALAM BINGKAI PROMISSIO YANG MEMAKNAI MISSIO DAN COMPROMISSIO - Cahyono Budi Wibowo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
The church is a visible fellowship of people from different cultures and plural societies in the name of Jesus. This is what is called the real church. Believing in the church means believing in the Lord Jesus' promise that when two or three people gather in His name, that is where He will be in the midst of them (Matthew 18:20). Believing in the church is believing that the church is a